2020
DOI: 10.1016/j.heliyon.2020.e04772
|View full text |Cite
|
Sign up to set email alerts
|

The effect of income inequality on carbon dioxide emissions: A case study of Indonesia

Abstract: The main objective of this study was to investigate the effect of income inequality on carbon dioxide (CO 2 ) emissions in Indonesia from 1975 to 2017 using the Autoregressive Distributed Lag (ARDL) technique. Per capita GDP, urbanization, and dependency ratio are included as additional variables in the analytical models. The statistical estimation and tests showed that income inequality has a negative effect on CO 2 emissions but the relationship pattern depends o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 53 publications
4
29
0
Order By: Relevance
“…to the EKC hypothesis (M. A. Baloch, Ozturk, et al, 2020;Dogan & Inglesi-Lotz, 2020;Kusumawardani & Dewi, 2020;Pata & Aydin, 2020;Sarkodie & Ozturk, 2020;Sharif et al, 2020), while others fail to con rm the hypothesis (Dogan & Ozturk, 2017;Dogan & Turkekul, 2016). Some of the studies that do not support the EKC hypothesis argue that the relationship between economic growth and environmental quality is linear (Gill et al, 2017).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…to the EKC hypothesis (M. A. Baloch, Ozturk, et al, 2020;Dogan & Inglesi-Lotz, 2020;Kusumawardani & Dewi, 2020;Pata & Aydin, 2020;Sarkodie & Ozturk, 2020;Sharif et al, 2020), while others fail to con rm the hypothesis (Dogan & Ozturk, 2017;Dogan & Turkekul, 2016). Some of the studies that do not support the EKC hypothesis argue that the relationship between economic growth and environmental quality is linear (Gill et al, 2017).…”
mentioning
confidence: 99%
“…The existing evidences regarding the impact of income inequality on environmental quality are quite mixed (Berthe & Elie, 2015;Knight et al, 2017). Findings of these studies vary depending on economic status of countries (Grunewald et al, 2017;Jorgenson et al, 2016;Kusumawardani & Dewi, 2020;Liobikienė, 2020;Magnani, 2000;Mittmann & de Mattos, 2020), time periods (Bhattacharya, 2019;Uddin et al, 2020), and modelling techniques used for the analysis (Hübler, 2017;Uddin et al, 2020). Jorgenson et al (2017) argued that the mixed ndings are attributed to several channels through which income inequality might affect emissions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…They also concluded that the EKC is valid in Turkey. Kusumawardani and Dewi (2020) tested the effect of income inequality on Indonesia's CO 2 emissions between 1975-2017. They used the ARDL method for analysis and determined that income inequality negatively affects CO 2 emissions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This quadratic effect is known as the EKC hypothesis (Grossman and Krueger, 1991). The EKC hypothesis presumes that the environmental degradation and income nexus is inverted-U shaped, not linear (Kusumawardani and Dewi, 2020).…”
Section: Introductionmentioning
confidence: 99%